2013
DOI: 10.4103/0976-500x.120957
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic burden of adverse drug reactions

Abstract: Adverse drug reactions (ADRs) are unwanted drug effects that have considerable economic as well as clinical costs as they often lead to hospital admission, prolongation of hospital stay and emergency department visits. Randomized controlled trials (RCTs) are the main premarketing methods used to detect and quantify ADRs but these have several limitations, such as limited study sample size and limited heterogeneity due to the exclusion of the frailest patients. In addition, ADRs due to inappropriate medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
298
1
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(317 citation statements)
references
References 64 publications
2
298
1
16
Order By: Relevance
“…[1][2][3] This is because the duration of the study was short; the nature of patients were different; the disease treated was not the same; when compared to use after approval and once more the majority of testing were conducted in animal-models which cannot guarantee human-safety. [1][2][3][4] In addition, information is lacking on drug-interactions, chronic-toxicity studies as well as use in neonates, pregnant and lactating women, geriatric patients, and patient with kidney or heart failure. 2 Therefore, in order to detect exceptional and unforeseen ADRs and ensure patient safety post-marketing surveillance has become indispensable Research reported that only 6-10% of the ADRs detected are reported to the authorities.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This is because the duration of the study was short; the nature of patients were different; the disease treated was not the same; when compared to use after approval and once more the majority of testing were conducted in animal-models which cannot guarantee human-safety. [1][2][3][4] In addition, information is lacking on drug-interactions, chronic-toxicity studies as well as use in neonates, pregnant and lactating women, geriatric patients, and patient with kidney or heart failure. 2 Therefore, in order to detect exceptional and unforeseen ADRs and ensure patient safety post-marketing surveillance has become indispensable Research reported that only 6-10% of the ADRs detected are reported to the authorities.…”
Section: Introductionmentioning
confidence: 99%
“…Questo rischio è determinato da svariati fattori quali, ad esempio, la dose e la frequenza di somministrazione, oppure le caratteristiche farmacocinetiche di specifiche popolazioni (pediatrica, geriatrica, con insufficienza renale ecc.) (39). Data l'elevata incidenza e le potenziali gravi conseguenze, gli EA generano un forte impatto sia clinico che economico.…”
Section: Discussioneunclassified
“…26,29 Recent studies have uncovered numerous genetic linkages with drug-induced toxicity and/or side effects, where knowledge of the individual genetic profile can indicate the likelihood of an undesirable outcome and direct the physician towards alternative medications if necessary and available. Abacavir and carbamazepine are two prime examples, especially as patients who do not carry the HLA-B*57:01 and HLA-B*15:02 alleles, respectively, for the two drugs will almost never experience abacavir-induced hypersensitivity or carbamazepine-induced Stevens-Johnson syndrome.…”
Section: Strengths Of Pharmacogenomics In Clinical Medicinementioning
confidence: 99%